2009
DOI: 10.1016/j.autrev.2008.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Altered B cell receptor signaling in human systemic lupus erythematosus

Abstract: Regulation of B cell receptor signaling is essential for the development of specific immunity while retaining tolerance to self. Systemic lupus erythematosus (SLE) is characterized by a loss of B cell tolerance and the production of anti-self antibodies. Accompanying this break down in tolerance are alterations in B cell receptor signal transduction including elevated induced calcium responses and increased protein phosphorylation. Specific pathways that negatively regulate B cell signaling have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…CCND3 is a key gene in B-cell development and differentiation, and there are many important activated signaling pathways that contribute to the abnormality of B cells in SLE patients, including IFNa, the BCR signaling pathway and the TLR7 pathway. 18,34,35 In this study, we found that other than the two other signaling pathways, only the activation of TLR7 increased the expression of CCND3. Thus, it is necessary for us to uncover the molecular mechanism of the TLR7 pathway in elevating CCND3 in active SLE.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…CCND3 is a key gene in B-cell development and differentiation, and there are many important activated signaling pathways that contribute to the abnormality of B cells in SLE patients, including IFNa, the BCR signaling pathway and the TLR7 pathway. 18,34,35 In this study, we found that other than the two other signaling pathways, only the activation of TLR7 increased the expression of CCND3. Thus, it is necessary for us to uncover the molecular mechanism of the TLR7 pathway in elevating CCND3 in active SLE.…”
Section: Discussionsupporting
confidence: 47%
“…18,34,35 To determine whether activation of those pathways could affect CCND3 expression in B cells, we stimulated mouse B cells with IFN-a (1000 U/mL), anti-IgM (5 mg/mL) or TLR7 agonist R848 (1 mg/mL) for 6 h or 24 h. Compared with the control, B cells treated with R848 showed a significant increase in the expression of CCND3 in a time course experiment, while treatment with IFN-a or anti-IgM did not show any significant difference (Figure 4a). The protein expression results were consistent with the transcriptional results (Figure 4b).…”
Section: Activation Of Tlr7 Elevates Ccnd3 Expression But Decreased Tmentioning
confidence: 99%
“…In this disease, BCR-constitutive activation was proven and potentially related to defective Fc␥RIIB signaling or/and circulating B-cell stimulator. 37 Our study raises the possibility that, in LE, RTX also acts through BCR inhibition.…”
Section: Discussionmentioning
confidence: 71%
“…Neurologic and psychiatric manifestations are common in SLE and occur in up to 75% of patients (Ballok, 2007). Pathophysiologically SLE is characterized by the dysfunction of T, B, and dendritic cells (DC), skewed cytokine production, breakdown of immunological tolerance, and the production of antinuclear autoantibodies (Jenks and Sanz, 2009;Crispín et al, 2010;Perl, 2010;Tsokos, 2011). The disturbance of the cytokine balance is implicated in the pathogenesis of SLE; therefore, cytokine balance might be a candidate target for treating SLE.…”
Section: Introductionmentioning
confidence: 99%